The image as a mind tool (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2017)
In last fifty years technology has made it incredibly easy to produce, edit and distribute still images and videos. We live submerged by a continuous flow of images and it is impossible to overestimate their importance in today’s society. Movies, animations, drawings and photographs are used primarily to communicate, but they also represent an instrument of thought: in fact one can use an image to understand more in depth a complicated concept or draw a diagram to follow the thread of a thin idea that, without a graphic representation, might get lost in the unconscious mind. It is possible to capture the sense of an entire mathematical demonstration with a single figure or to graphically compute the solution of a problem with a sequence of diagrams; but one can also put on paper an error or a paradox. Even in painting there are example where the aesthetic aspect is inextricably linked to the solution of a complicated and interesting problem. In the following pages, ten images will attempt to illustrate these concepts. Moreover using images in this context is a self–referential action that reminds of the extraordinary ability to reflect on itself that is a feature of the mind.